2020
DOI: 10.21203/rs.3.rs-24562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practices (KAP) towards COVID-19 and assessment of risks of infection by SARS-CoV-2 among the Bangladeshi population: An online cross sectional survey

Abstract: The COVID19 pandemic has been transmitted worldwide rapidly. The best ways of preventing this virus are to know about and act accordingly. An online cross sectional survey was conducted to know the knowledge, attitude and practices towards COVID19 and to assess the risks of infections among Bangladeshi population. Among 2045 respondents, 54·87% respondents kept good knowledge. Knowledge was significantly diverged across age, gender, education levels, residences, income groups, and marital status. Despite the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
76
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 9 publications
23
76
7
1
Order By: Relevance
“…This study also identi ed that majority of the Bangladeshi young adults access knowledge regarding COVID-19 mainly through social media such as Facebook which is analogous with a recent COVID-19 study conducted by Farhana, (2020). This nding also justi ed by the fact that a vast majority of Bangladeshi young adults relying on the internet and social media in their regular lifestyle and during lockdown initiative amid COVID-19 which is increased by 15-20% (Hossain 2020).A substantial number of sociodemographic factors signi cantly affect participant's knowledge scores such as age-groups, genders, education levels, socio-economic classes, and places of residence which were quite similar to a study byHaque et al (2020). Multiple regression analysis found participant's adequate knowledge was dominated by factors such as gender, marital status, education, and place of residence.…”
supporting
confidence: 77%
“…This study also identi ed that majority of the Bangladeshi young adults access knowledge regarding COVID-19 mainly through social media such as Facebook which is analogous with a recent COVID-19 study conducted by Farhana, (2020). This nding also justi ed by the fact that a vast majority of Bangladeshi young adults relying on the internet and social media in their regular lifestyle and during lockdown initiative amid COVID-19 which is increased by 15-20% (Hossain 2020).A substantial number of sociodemographic factors signi cantly affect participant's knowledge scores such as age-groups, genders, education levels, socio-economic classes, and places of residence which were quite similar to a study byHaque et al (2020). Multiple regression analysis found participant's adequate knowledge was dominated by factors such as gender, marital status, education, and place of residence.…”
supporting
confidence: 77%
“…Our knowledge averages were lower than the aforementioned studied although in our case the data collection was done at a much later time, a time at which global public awareness towards COVID-19 was on the rise. On the other hand, a similar study in Bangladesh found that the correct knowledge average was 54•87% which was less than our ndings [21] while another study conducted in Egypt obtained almost the same correct knowledge percentage (71.2%) [22].…”
Section: Discussioncontrasting
confidence: 87%
“…Regarding the use of personal protective equipment (PPE), such as gloves, masks or face shields, we found that only 39.2% of our sample always used them. This is a low percentage when compared to the 98.0% of people always wearing facemasks when going out in the Chinese study [18]; 95.45% in Bangladesh [21] and even the 51.2% that was found by Azlan et al 2020 [19]. Such a low percentage in our study could be attributed to the lack of clear public policy by the Lebanese government which did not impose PPE's at the time our data was collected (the government implemented the lock down and prevention campaign at the time where this survey was conducted but the control of the implementation of this strategy was not strict).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The copyright holder for this this version posted September 18, 2020. ; https://doi.org/10.1101/2020.09.15.20195255 doi: medRxiv preprint perceptions of COVID-19 (15). Another Bangladeshi study found despite 54.9% respondents kept good knowledge but the attitude and practices were not impressive mainly because of poor knowledge, non-scientific, and orthodox religious belief (16).…”
Section: Introductionmentioning
confidence: 99%